Assessing Progress in Reducing the Number of Disaster-affected People: Insights from Zimbabwe - Mavhura, Emmanuel (Global Journal of Earth Science and Engineering, 2023)
In 2015, 187 countries appended their signatures to the Sendai Framework for Disaster Risk Reduction. This framework has seven global targets which need to be monitored both at national and global levels. In order to promote the monitoring and reporting on progress in attaining the global targets, the United Nations Office for Disaster Risk Reduction provided some technical guidance notes and methodologies. Using the case study of Zimbabwe, this study used the technical guidance notes and methodologies to assess the country’s progress in reducing the number of people affected by disasters. Quantitative data for this assessment came from public sources published by the Government of Zimbabwe spanning the period 1990 to 2019. This data was analysed using 3-year and 5-year moving averages. In addition, the study used qualitative interviews to explain the trends in the number of people affected by disasters. Results showed slight decreases in the number of people affected by both aggregated and disaggregated disasters. Drought disasters emerged as the only one that affected millions of people yearly. However, storms and epidemics were sporadic and characterised by big spikes. The study concluded that Zimbabwe is slowly attaining Target B. The study further offered three policy implications that are meant to significantly reduce the number of people affected by disasters. This includes the need to strengthen drought preparedness/mitigation, and disease surveillance and control systems.